Identification of protein kinase C beta as a therapeutic target for neuroendocrine prostate cancer and development of a nanoparticle-based therapeutic strategy. (February 2023) - Qie, Yunkai; Cheng, Zhaoxia; Wu, Zhouliang; Qi, Feilong; Li, Bozhao; Wu, Suying; Chu, Tianjiao; Lu, Zefang; Li, Suping; Nie, Guangjun
Abstract: Neuroendocrine prostate cancer (NEPC) is a highly aggressive subtype of malignant prostate cancer for which there is no effective treatment. Although protein kinases are the most attractive therapeutic targets for cancer treatment, there are no clear kinase-targeted drugs available for NEPC treatment. Herein, we showed that protein kinase C beta (PKCβ) is highly expressed in NEPC and can be transcriptionally activated by c-Myc through the E-box elements present in its promoter region. Furthermore, PKCβ can activate PIM1 kinase by phosphorylating Ser51 and Ser54, which in turn stabilizes and enhances c-Myc function. Three formed a PIM1-c-Myc-PKCβ positive feedback loop to promote the progression of NEPC. Enzastaurin, a specific inhibitor of PKCβ, significantly ameliorated NEPC. However, enzastaurin causes thrombus and other side effects in several clinical trials of other diseases, which greatly limits its clinical application. To address these problems, we developed a functional polymer nanoparticle modified with SSTR2-targeted octreotide and a thrombin-binding aptamer to deliver enzastaurin for NEPC treatment. The tailor-designed nanomedicine efficiently retards tumor growth and the incidence of coagulation abnormalities in vitro and in vivo . Collectively, our findings highlight the key role of PKCβ in NEPC and provide a promising nanoparticle-based therapeutic strategy for the treatment of NEPC. Graphical Abstract: ga1 Highlights: Identifying PKCβ as a new therapeutic target for NEPC. PKCβ drive the progression of NEPC through a PIM1-c-Myc-PKCβ positive feedback loop. Developing a functional polymeric nanoparticle to deliver enzastaurin in the treatment of NEPC. The tailor-designed nanomedicine should be a promising therapeutic strategy for NEPC treatment.